PENGARUH LOKASI DAN KUALITAS MAKANAN TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA WARUNG TANJUNG DI SITUBONDO - Firdaus, Mohammad Alaikal; Ediyanto, Ediyanto; Tulhusnah, Lusiana (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
This study aims to determine the effect of location and food quality on consumer loyalty with consumer satisfaction as an intervening variable at Warung Tanjung in Situbondo. This type of research is quantitative. The population of this study were visitors to Warung Tanjung in Situbondo. The sampling technique was determined by probability sampling with simple random sampling of 95 respondents. Data analysis and hypothesis testing in this study used the Structural-Partial Least Square (PLS) Equation Model. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that the location has a significant positive effect on consumer satisfaction. Food Quality has a significant positive effect on Consumer Satisfaction. Location has a positive but not significant effect on Consumer Loyalty. Food Quality has a positive but not significant effect on Consumer Loyalty. Location has a significant positive effect on Consumer Loyalty through Consumer Satisfaction. Food Quality has a significant positive effect on Consumer Loyalty through Consumer Satisfaction.